1998
DOI: 10.1037/0022-3514.74.3.715
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between racial identity and self-esteem in African American college and high school students.

Abstract: The Multidimensional Model of Racial Identity was used to examine the relationship between racial identity and personal self-esteem (PSE) in a sample of African American college students (n = 173) and a sample of African American high school students (n = 72). Racial identity was assessed using the Centrality and Regard scales of the Multidimensional Inventory of Black Identity, whereas the Rosenberg Self-Esteem Scale was used to assess PSE. Riur predictions were tested: (a) racial centrality is weakly but pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
278
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(308 citation statements)
references
References 56 publications
23
278
2
1
Order By: Relevance
“…A wealth of previous research has focused on psychological aspects of African-American identity [34], including associations with self-esteem [59] and academic performance [60]. Yet, there is no clear consensus among psychological identity theorists over whether strong identification with racial group places individuals of African descent at risk for adverse effects or whether such identification serves as a protective factor which promotes resiliency against racism and discrimination [34,61,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of previous research has focused on psychological aspects of African-American identity [34], including associations with self-esteem [59] and academic performance [60]. Yet, there is no clear consensus among psychological identity theorists over whether strong identification with racial group places individuals of African descent at risk for adverse effects or whether such identification serves as a protective factor which promotes resiliency against racism and discrimination [34,61,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Group identification provides individuals with a social and psychological 'place' within which they can establish a sense of meaning and identity (Simon, 1999;Spears, Jetten, & Scheepers, 2002). Minority group identification is correlated with psychological adjustment among a number of different kinds of stigmatized groups (Bat-Chava, 1994;Grossman, Wirt, & Davids, 1985;Munford, 1994;Phinney, 1990;Rowley, Sellers, Chavous, & Smith, 1998), and experimental work has found that the mere presence of similarly stigmatized others raises self-esteem and lowers depression and anxiety (Frable, Pratt, & Hoey, 1998;McKenna & Bargh, 1998). Furthermore, regardless of the ingroup's status, identification with ingroup social categories is associated with positive well-being (Branscombe & Wann, 1991).…”
Section: The Psychological Costs Of Exclusionmentioning
confidence: 98%
“…Models of racial/ethnic identity were developed which suggest that individuals move from having naïve beliefs about their racial group status, holding negative feelings about their racial group, or placing low salience on race, to developing racial consciousness and a sense of pride in history, heritage, and group membership (Schwarzbaum and Thomas 2008). Positive racial identity has been found to be related to positive outcomes in African American youth, including positive self-esteem (Buckley and Carter 2005;Greene et al 2006;Rowley et al 1998;Sellers et al 2006), reduced psychological symptoms, particularly depression and anxiety (Sellers et al 2006), and higher levels of academic achievement (Altschul et al 2006;Jagers et al 1997;Wong et al 2003). Racial identity seems to serve as a buffer for acts of racism, discrimination, or prejudice (Greene et al 2006).…”
Section: Gendered Racial Identity Of Black Young Womenmentioning
confidence: 99%